If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -870 = -15(13x + -33) Reorder the terms: -870 = -15(-33 + 13x) -870 = (-33 * -15 + 13x * -15) -870 = (495 + -195x) Solving -870 = 495 + -195x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '195x' to each side of the equation. -870 + 195x = 495 + -195x + 195x Combine like terms: -195x + 195x = 0 -870 + 195x = 495 + 0 -870 + 195x = 495 Add '870' to each side of the equation. -870 + 870 + 195x = 495 + 870 Combine like terms: -870 + 870 = 0 0 + 195x = 495 + 870 195x = 495 + 870 Combine like terms: 495 + 870 = 1365 195x = 1365 Divide each side by '195'. x = 7 Simplifying x = 7
| 87-19=68 | | -1=3n-1-4n | | y/3-x/2=1 | | 1.2x+0.3y=3.8 | | (5z^6x^5)/(8z^2)*(1x^3)/(3z^2x^3) | | v(m)=34000-0.2m | | 6.5-4.5(1+9.5b)=23.5 | | log(x-5)-log(16)=log(8) | | -12(-9x+23)=480 | | v=34000-0.2m | | 0=x-7x^(1/7) | | 0=1-x^(-6/7) | | 5x-10=2(8x+6) | | 882=9(-9x-10) | | 0.60x+0.15(80)=0.50(x+80) | | 4a+20=5b+7 | | 12(4-5x)=44 | | -0.1x+0.3y=-2 | | b^2-4b-14=-1 | | 4a-5b=-13 | | 12x-236=76+18x | | 3.4=400a+20b | | 2/5h-16=3/5h-14 | | t=7-10(39-1) | | -6x+7(-3x-34)=32 | | t=-6+4(15-1) | | 4x^2+x=-4 | | t=19+6(52-1) | | 0=8x^2+8x+1 | | 115-1/6 | | 251-17x=-9x-285 | | t=-38-7(52-1) |